PENGARUH SHOPPING LIFESYTLE, PRICE DISKON DAN DISPLAY PRODUCT TERHADAP IMPULSE BUYING - Adhitya Yoga Prasetya; Refo Iman Syukur Telaumbanua; Dhian Andanarini Minar Savitri (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2020)
This study (Case Study Of Transmart Setia Budi Semarang-PT.Trans Retail Indonesia) aims to examine how shopping habits, price reductions, and product displays influence implausible purchasing. The shopping lifestyle, price discounts, product display, and impulse buying are the dependent variables analyzed in this study. In this study, questionnaires were distributed to 76 respondents who had made impulsive purchases in Semarang faithful transmart. This was a purposive sampling method. The validity and reliability tests, classic assumption tests, normality tests, multiple linear regression tests, the feasibility test of a model (F test), the individual parameter significance test (t statistical test), and the terminated coefficient test (R2) were used in this study's data analysis with the assistance of the spss program. The outcomes showed that shopping way of life affected motivation purchasing, cost markdown meaningfully affected drive purchasing, and show items significantly affected drive purchasing.